Checklist of helminth parasites of Goodeinae (Osteichthyes: Cyprinodontiformes: Goodeidae), an endemic subfamily of freshwater fishes from Mexico - Martínez-Aquino, Andrés; Mendoza-Palmero, Carlos A; Aguilar-Aguilar, Rogelio; Pérez-Ponce de León, Gerardo (Zootaxa, 2014)
From August 2008 to July 2010, 1,471 fish belonging to the subfamily Goodeinae (representing 28 species) were collected from 47 localities across central Mexico and analyzed for helminth parasites. In addition, a database with all available published accounts of the helminth parasite fauna of goodeines was assembled. Based on both sources of information, a checklist containing all the records was compiled as a necessary first step to address future questions in the areas of ecology, evolutionary biology and biogeography of this host-parasite association. The checklist is presented in two tables, a parasite-host list and a host-parasite list. The checklist contains 51 nominal species, from 34 genera and 26 families of helminth parasites. It includes 8 species of adult digeneans, 9 metacercarie, 6 monogeneans, 3 adult cestodes, 9 metacestodes, 1 adult acanthocephalan, 1 cystacanth, 6 adult nematodes and 8 larval nematodes. Based on the amount of information contained in the checklist, we pose that goodeines, a subfamily of viviparous freshwater fishes endemic to central Mexico, might be regarded as the first group of wildlife vertebrate for which a complete inventory of their helminth parasite fauna has been completed.
Keywords: cizopasní červi; nemoci ryb; Cyprinodontiformes; Mexiko; Animals; Fish Diseases; Helminthiasis, Animal; Helminths; zvířata; Mexico; kontrolní seznam; Checklist; helmintózy zvířat